Novel carbon materials: new tunneling systems (Review Article) - Strzhemechny, M.A.; Dolbin, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
This review covers recent achievements in the studies of quantum properties of the novel carbon materials (fullerite C60 and bundles of single-walled nanotubes (SWNT)) saturated with such light-mass species as helium isotopes, the homonuclear molecular hydrogens, and neon. It is shown that even some heavy dopants demon-strate kinetic phenomena, in which coherent effects play an essential role. Two theoretical concepts are surveyed which have been suggested for the explanation of the anomalous phenomena in saturation kinetics and linear thermal expansion of doped C60. Most unusual effects have been also observed in the low-temperature radial ex-pansion of bundles of single-walled carbon nanotubes saturated with the helium isotopes. First, it was shown that low-temperature radial expansion of pure SWNT is negative, i.e., a nanotube shrinks with warming. Second, saturation of SWNT bundles with the helium isotopes entails a huge increase of the negative expansion effect, when the dopant is He. So far, no detailed physical picture has been put forward. It is worth mentioning that the dynamics of a single helium atom on an isolated nanotube corresponds to that of a tight-bound quasiparticle with a band width of about 10 K.